Efficient GDI-based approximate subtractors for change detection in bio-image processing applications. (May 2023) - Pooladi, Fatemeh; Pesaran, Farshad; Shiri, Nabiollah
Abstract: Three new approximate subtractors are presented based on the gate diffusion input (GDI) technique which benefits from the dynamic threshold (DT) technique using carbon nanotube field-effect transistors (CNTFETs) technology. Proposed-1, Proposed-2, and Proposed-3 subtractors have 10, 8, and 6 transistors with a total area of 0.289 μm 2, 0.123 μm 2, and 0.065 μm 2, respectively. In Proposed-1 and Proposed-2, only XOR and F1 gates are used, which respectively have 2 and 4 errors. To solve the non-full-swing defects of these two circuits, only three F2-GDI gates are used in the Proposed-3, which has 4 errors. The Proposed-1 gives 0.25 as error distance (ED) while two other circuits with a lower area have an ED of 0.5. The Proposed-3 has a simple, low-power, and ground-free structure. The subtractors are implemented in an 8 to 4 non-restoring divider in four different configurations including vertical, horizontal, square, and triangular. The drivers based on Proposed-2 and Proposed-3 are the best circuits with average power-delay-product (PDP) savings of 68.16% and 57.43%, respectively. Finally, the dividers are used in the change detection of medical images, where, the proposed circuits show better circuitry performance and image quality production.